Legal Consequences and the Role of Notaries on the Deed of Establishment of the Foundation Pre and After the Enactment of the Foundation Law (Case Study of Deed of Establishment of Christian College Service Provider Foundation No.17 of 1991 and Deed of Establishment of Christian College Service Provider Foundation No. 2 of 2011) - Timotius Eric Haryanto (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The case study in this legal research is Yayasan Penyelenggara Pelayanan Perguruan Kristen (YPPPK) which exist two Deed of Establishment, namely in 1991 and in 2011. The purpose of this legal research is to determine the legal consequences of the deed of establishment and the role of public notary before and after the enactment of the foundation law on YPPPK’s Deed of Establishment in 1991 and 2011. The research method is normative with a statutory, case, and conceptual approach. The data used are secondary data obtained from research literature including primary, secondary and tertiary legal sources. The results of the research is that YPPPK should be liquidated or made a Deed of Meeting Resolution contain statement regarding the resemblance of YPPPK 2011 and 1991, because when the Foundation adjusted their Articles of Association towards the Law on Foundation, the Notary did not conducted their role properly which is making a deed in accordance to Government Regulation No. 2 of 2013 after the establishment of Law on Foundation. Keywords: Foundation; Deed of Establishment.